Characterization of Protistan Assemblages in the Ross Sea, Antarctica, by Denaturing Gradient Gel Electrophoresis - Gast, Rebecca J. (American Society for Microbiology, 2004)
The diversity of protistan assemblages has traditionally been studied using microscopy and morphological characterization, but these methods are often inadequate for ecological studies of these communities because most small protists inherently lack adequate taxonomic characters to facilitate their identification at the species level and many protistan species also do not preserve well. We have therefore used a culture-independent approach (denaturing gradient gel electrophoresis [DGGE]) to obtain an assessment of the genetic composition and distribution of protists within different microhabitats (seawater, meltwater or slush on sea-ice floes, and ice) of the Ross Sea, Antarctica. Samples of the same type (e.g., water) shared more of the same bands than samples of different types (e.g., ice versus water), despite being collected from different sites. These findings imply that samples from the same environment have a similar protistan species composition and that the type of microenvironment significantly influences the protistan species composition of these Antarctic assemblages. It should be noted that a large number of bands among the samples within each microhabitat were distinct, indicating the potential presence of significant genetic diversity within each microenvironment. Sequence analysis of selected DGGE bands revealed sequences that represent diatoms, dinoflagellates, ciliates, flagellates, and several unidentified eukaryotes.